String theory and cosmology : (Physica Scripta, Royal Swedish Academy of Sciences,World Scientific, 2005)
The Nobel Symposium in 2003 on String Theory and Cosmology was a gathering of many of the most active and distinguished scientists in the world, including Stephen Hawking, 2004 Nobel Prize winner David Gross, and Andrei Linde. The experts, comprising both theoreticians and experimentalists, were given the opportunity to discuss the present status of their respective subjects. Throughout the symposium, special attention was given to the connections between the fields: the questions posed ranged from "Can cosmology be used to test string theory?" to "Can string theory answer deep questions about cosmology?" The symposium marked a new era in the understanding of the science of the very small and the very large. This book is a unique document that reflects upon the state of fundamental physics at a historically important moment in time.